1997
DOI: 10.1207/s15327817la0603_2
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Violation and Phonological Development

Abstract: This articl-, examines some consequences of optimality theoretic constraint ranking and violability for the study of phonological deyelopment. It is well known that the phonetic shape of child utterances is subject to strict restrictions. When these restrictions are captured in terms of minimally violable, rather than inviolable, constraints, the effects of a constraint that is overcome in development can continue to persist through successive developmental stages and into the mature system. The empirical base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0
20

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(177 citation statements)
references
References 6 publications
(16 reference statements)
9
148
0
20
Order By: Relevance
“…15 Some studies have reported evidence from English children's early productions suggesting that unfooted weak syllables are more prone to omission than footed weak syllables (Gerken 1996;Pater 1997;McGregor and Johnson 1997). However, the authors have interpreted this phenomenon as supporting the binary trochee as the preferred target structure in children's output forms.…”
Section: Alternative Representational Analysesmentioning
confidence: 99%
“…15 Some studies have reported evidence from English children's early productions suggesting that unfooted weak syllables are more prone to omission than footed weak syllables (Gerken 1996;Pater 1997;McGregor and Johnson 1997). However, the authors have interpreted this phenomenon as supporting the binary trochee as the preferred target structure in children's output forms.…”
Section: Alternative Representational Analysesmentioning
confidence: 99%
“…This favours the learning of restrictive final grammars, and also allows intermediate stages of child language acquisition to be more effectively modeled (Demuth 1995, Gnanadesikan 2004, Hayes 2004, Pater 1997, Smolensky 1996, Tessier 2007. The primary determinant of both sequence and rate of acquisition in this model is the distribution of inputs forms to which the learner is exposed.…”
Section: Model Predictionsmentioning
confidence: 99%
“…Echols and Newport 1992;Gerken 1996;Pater 1997. ) With respect to the stressed syllable position, Kehoe and Stoel-Gammon (1997) and Kehoe (2000) report on an elicitation study of English-speaking children at 2;4 and 2;10, designed in part to test for stress effects on syllable truncation.…”
Section: Intermediate Faith To English Stressed Syllablesmentioning
confidence: 99%
“…This one-foot stage in phonological development has often been derived using gradient Align (Ft, PWd) constraints (e.g. Pater 1997), but in light of McCarthy (2003)'s influential arguments against such gradient constraints an alternative analysis is called for. 9 In fact, McCarthy (2003) re-interprets single foot (i.e.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation